Heterogeneous DNA methylation status in same-cell subpopulations of ovarian cancer tissues. Issue 6 (May 2017) - Li, Qiling; Xue, Xue; Li, Wenzhi; Wang, Qi; Han, Lu; Brunson, Tiffany; Xu, Wei; Chambers-Harris, Isfahan; Wang, Qing; Li, Xu; Ma, Li; Song, Qing
This study aims to explore the heterogeneous DNA methylation differences between individual single ovarian cancer cells isolated from the same formalin-fixed and paraffin-embedded human ovarian cancer tissue. Single cells were isolated by laser microdissection. Whole genome amplification and polymerase chain reaction purification were performed on the converted genomic DNA. Target primers designed for checking DNA methylation were used in polymerase chain reaction reactions to amplify special fragments. Sequencing was performed to analyze the heterogeneous DNA methylation statuses of different single ovarian cancer cells. Three of nine single human ovarian cancer cells showed positive bands (33.3%) on separating gel. The methylated and unmethylated CpGs were shown at the same loci in different single cells. We show heterogeneous DNA methylation statuses in same-cell subpopulations.